ECOLOGICAL TOURISM: DEVELOPMENT, ADVANTAGES AND DISADVANTAGES - Valentin Dmitrievich Ivanov (Физическая культура. Спорт. Туризм. Двигательная рекреация, 2020)
This article is dedicated to ecological tourism, discovering its history and showing development from the earlier days up to anon. Also, it refers to its its benefits and faults, its impact on the economy and nature. It includes information about development of the above mentioned form of tourism not only in the European Union countries but additionally refers to the destinations like Zimbabwe, South Africa, Kenya and Costa Rica. The required conclusion is made summing up all mentioned in the article.